2013
DOI: 10.1111/j.1525-1594.2012.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Effects of Bretschneider's Histidine‐Tryptophan‐Ketoglutarate and Conventional Crystalloid Cardioplegia on Pediatric Myocardium at Tissue Level

Abstract: Cardioplegic arrest is one of the most common myocardial protection strategies. A wide variety of cardioplegic solutions are routinely being used. There is an ongoing discussion about the relative effectiveness of these solutions considering myocardial protection. This study aims to investigate the hypothesis that the use of histidine-tryptophan-ketoglutarate (HTK) cardioplegia leads to decreased ischemic damage on myocardium compared with the use of conventional crystalloid cardioplegia. The study population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…In this study, no other differences in postoperative values across the two groups could be demonstrated on clinical levels. This result was similar to Korun's study which found no clinically or histopathologically detectable difference between the two solutions (18). In Korun's study the mean ACC time was about 70 min and about 80 min in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, no other differences in postoperative values across the two groups could be demonstrated on clinical levels. This result was similar to Korun's study which found no clinically or histopathologically detectable difference between the two solutions (18). In Korun's study the mean ACC time was about 70 min and about 80 min in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Data collected from instances in which HTK solution has been used for high-risk patients with complex congenital heart disease remains rare (19)(20)(21)(22). A study of Fuwai Hospital compared the myocardial protective effect induced by HTK solution and conventional St. Thomas crystalloid cardioplegia on the long-term ischemic period (cross-clamping time, >90 min) during severe complex pediatric cardiac surgery without pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Bretschneider (histidine-tryptophan-ketoglutarate, HTK) solution is routinely administered for cardioplegic arrest in many countries (Careaga et al 2001 ). In clinical studies as well as in experimental models the Bretschneider solution has been shown to achieve a better myocardial protection during ischemia as compared to pure electrolyte-containing crystalloid cardioplegic solutions without histidine or to blood cardioplegia (Beyersdorf et al 1990 ; Careaga et al 2001 ; Kober et al 1998 ; Korun et al 2013 ; Sakata et al 1998 ; Scrascia et al 2011 ). The effectiveness of the solution becomes apparent in an increased cardiac output, fewer arrhythmias, more frequent spontaneous defibrillation as well as decreasing length of stay in the intensive care unit (Careaga et al 2001 ; Sakata et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%